Evaluating the Long-Term Impact of Sustainable Tourism Practices on Local Communities and Natural Resources in Developing Countries - Bentley, Leo; Halim, Homaira Binte (Integrated Journal for Research in Arts and Humanities, 2024)
This study evaluates the long-term impact of sustainable tourism practices on local communities and natural resources in developing countries. Utilizing a mixed-methods approach, we conducted case studies in regions known for their biodiversity and tourism reliance. Quantitative data was collected through environmental monitoring and economic indicators, while qualitative insights were obtained from interviews with local stakeholders. The findings indicate that sustainable tourism practices contribute to environmental preservation and provide economic benefits to local communities. However, the success of these practices is contingent on robust policy frameworks, community engagement, and ongoing education. Despite initial positive outcomes, challenges such as inadequate infrastructure, limited funding, and governance issues persist. This research underscores the importance of tailored sustainable tourism strategies that address specific local contexts and promotes the integration of comprehensive management plans to ensure long-term sustainability. Recommendations for policymakers and practitioners are provided to enhance the efficacy of sustainable tourism initiatives in developing countries.